Thymoma and thymic carcinoma in children and adolescents: The EXPeRT/PARTNER diagnostic and therapeutic recommendations. (21st April 2021) - Stachowicz‐Stencel, Teresa; Synakiewicz, Anna; Cornet, Marianna; Ferrari, Andrea; Garassino, Marina; Masip, Jordi Remon; Julien, Rod; Virgone, Calogero; Schneider, Dominik T.; Brecht, Ines B.; Ben‐Ami, Tal; Bien, Ewa; et al.
Abstract: Thymic tumors are epithelial tumors arising from the anterior mediastinum and constitute 0.2–1.5% of all adult malignancies but are exceptional in pediatric population. Thymic epithelial tumors (TETs) encompass a variety of histologic subtypes associated with different clinical outcomes. Due to its rarity in children, TETs' management requires a multidisciplinary approach. However, prognosis remains still poor, especially among patients with thymic carcinoma. This study presents the internationally recognized recommendations for the diagnosis and treatment of thymic tumors in children and adolescents, established by the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) group within the EU‐funded project Paediatric Rare Tumours Network ‐ European Registry (PARTNER).